Assessing the Economic Impact of Bridge Construction on the Gili Ree Hamlet Community, Lombok Timur Regency, Indonesia - Anis Aulida Suriyani; Sahri, Sahri; M. Firmansyah; Amin , Abdullah Al; Funda Yavuz (Tinta Emas Publisher, 2024)
This study aims to determine how the impact of bridge construction on the economic conditions of the people of Gili Ree hamlet, Paremas village, Jerowaru sub-district, Lombok Timur district. The approach used is a qualitative approach, which uses descriptive methods. With primary data and secondary data derived from selected informants, namely the head of Gili Ree hamlet as a key informant and people who work as fishermen and traders as the main informants, using purposive and snow ball methods. The results of this study indicate that the impact of bridge construction on the economic conditions of the Gili Ree hamlet community is the smooth distribution of goods and services, an increase in business turnover and changes in asset use while other impacts arising from the existence of this bridge are able to facilitate the accessibility of children to go to school and the smoothness of access between Gili Ree Hamlet and Gili Belek Hamlet becomes easier.